Entropy lowering in ion-atom collisions - Nguyen, H.; Brédy, R.; Lee, T. G.; Camp, H. A.; Awata, T.; DePaola, B. D. (My University, 2005)
In ion-atom collisions, the charge transfer cross section is typically a strong function of the energy defect or Q value, typically with smaller energy defects giving rise to higher capture probabilities. In some theoretical treatments, for example those based on the Demkov model, the cross section is a strong function of the magnitude of the Q value, but is independent of its sign. In order to test this predicted sign independence, one must compare capture cross sections from energetically symmetric collision channels. In this work, relative capture cross sections, differential in scattering angle, are measured and compared for the energetically symmetric channels: Rb++Rb(5s)→Rb(5p)+Rb+ and Rb++Rb(5p)→Rb(5s)+Rb+. It is found that not only are the two cross sections not equal, but that in this case the endoergic channel was 3 times more likely. That is, the entropy reducing channel was preferred. An intuitive model, based on molecular potential curves, is suggested. The endoergic propensity is found to be consistent with this model.